2009
DOI: 10.1111/j.1471-0528.2009.02143.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal anthropometrics are associated with fetal size in different periods of pregnancy and at birth. The Generation R Study

Abstract: Objective We aimed to examine the associations of maternal anthropometrics with fetal weight measured in different periods of pregnancy and with birth outcomes.Design Population-based birth cohort study.Setting Data of pregnant women and their children in Rotterdam, the Netherlands.Population In 8541 mothers, height, prepregnancy body mass index (BMI) and gestational weight gain were available.Methods Fetal growth was measured by ultrasound in mid-and late pregnancy. Regression analyses were used to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
98
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 38 publications
9
98
1
1
Order By: Relevance
“…We observed that maternal obesity and excessive gestational weight gain were associated with an increased risk of largesize-for-gestational-age infants and a lower risk of small-size-forgestational-age infants. Similar findings have been reported by other studies (4,17,18). Previously, we have shown that maternal prepregnancy BMI is positively associated with birth weight of the offspring (4).…”
Section: Obesitysupporting
confidence: 80%
See 3 more Smart Citations
“…We observed that maternal obesity and excessive gestational weight gain were associated with an increased risk of largesize-for-gestational-age infants and a lower risk of small-size-forgestational-age infants. Similar findings have been reported by other studies (4,17,18). Previously, we have shown that maternal prepregnancy BMI is positively associated with birth weight of the offspring (4).…”
Section: Obesitysupporting
confidence: 80%
“…Excessive gestational weight gain might also influence the risk of adverse maternal and fetal outcomes (4,5,7). The mechanisms of these associations remain unclear, as gestational weight gain reflects both maternal nutritional status, as well as tissue expansion during pregnancy, because of fat storage and fluids (4). Not much is known about the specific risk factors for maternal obesity and excessive weight gain during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 There is strong evidence for the association between maternal obesity and high infant birthweight. [2][3][4][5] Therefore, an increase in the prevalence of large-for-gestationalage (LGA) infants is likely, considering the increasing prevalence of obesity. 1,6 LGA infants are at increased risk of both short-and long-term poor outcomes, such as adult obesity and metabolic disease.…”
Section: Introductionmentioning
confidence: 99%